Tourism in a VUCA world : managing the future of tourism - Ul Islam, Naser; Chaudhary, Manjula; Vukadin, Izidora Marković (Emerald Publishing Limited, 2024)
The international tourism industry grew exponentially during the latter part of the 20th and early 21st century due to the advent of cheap air travel and a growing moneyed class. However, it witnessed a calamitous slowdown during the COVID-19 pandemic, when the world came to a standstill and was unable to travel. It brought to the fore the fragility of the tourism industry in the face of bio-threats and other uncertainties such as climate change, disease, war, and terrorism. These issues have led to a growing need for a strategic re-evaluation of the tourism industry vis-a-vis volatility, uncertainty, complexity, and ambiguity (VUCA) in the environment. Tourism in a VUCA World: Managing the Future of Tourism is an attempt to identify the new approaches to tourism in the near past, present, and future. Novel solutions can be expected through an integration of knowledge from the fields of social, physical, and biological sciences.
Keywords: Tourism -- Management.; Uncertainty.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books